Odrębność wydziałów kościelnych Uniwersytetu Kardynała Stefana Wyszyńskiego w Warszawie w świetle prawa kanonicznego - Domaszk, Arkadiusz (Prawo Kanoniczne, 2009)
The public University of the Cardinal Stefan Wyszynski in Warsaw (UKSW) came into being from the transformation in 1999 from the ecclesiastical college – Academy of the Catholic Theology. The statutes UKSW bases the activity of the University on Polish right, also that within the framework of UKSW are the place for ecclesiastical faculties: The Faculty of the Theology, The Canon Law Faculty and the Faculty of the Christian Philosophy. The originality of these faculties gets out of their directing on the Christian Revelation and the realization of the evangelization mission on the scientific ground. A second factor distinctive from other faculties UKSW is the dependence from the canonical right, at the simultaneous observance of the Polish law. The article showed that three church faculties UKSW kept their own canonical status. This legal status confirm records of the law the Right about the higher educational system (2005 year). Ecclesiastical faculties UKSW in Warsaw compose the perfect foot-bridge for the dialogue between the faith and the mind. Across their own investigative space fill up research of other sciences with which determine universitas. These departments are an important part of the University.